Impact of COVID-19 on testing, positive cases, patient characteristics, and hospital contacts for respiratory syncytial virus, influenza, and pneumococcus in Danish children - Andreas Jensen; Lone Graff Stensballe (Journal of Infection and Public Health)
Background: Respiratory infections substantially impact pediatric health. The COVID-19 pandemic introduced widespread non-pharmaceutical interventions, which influenced the incidence of common respiratory infections. This comprehensive study investigates the impact of these interventions on the incidence of respiratory syncytial virus, influenza, and invasive pneumococcal disease in Danish children. Methods: We conducted a descriptive study based on a cohort of 1,790,464 Danish children from 2012 to 2022. We analyzed data from microbiology tests and hospital contacts to assess infection rates and testing patterns before, during, and after the COVID-19 pandemic. The relationships between testing and sex, age groups, chronic disease status, and hospital contacts were analyzed. Results: We observed a marked decrease in cases of respiratory syncytial virus, influenza, and pneumococcus disease during the lockdown period. Once restrictions were lifted, there was a substantial resurgence in these infections. The frequency of testing for respiratory pathogens increased over time, with a rising proportion of healthy individuals without underlying chronic disease being tested. The proportion of positive tests linked to hospital contacts varied: there was a notable decline for respiratory syncytial virus and influenza post-lockdown, while pneumococcus cases continued to be strongly linked to hospital contacts. Conclusion: The study highlights the impact of COVID-19 interventions on the epidemiology of pediatric respiratory infections, revealing a pattern of decreased incidence during lockdowns followed by a resurgence. More tests were carried out among an increasing proportion of healthy individuals. Such changes in testing practices and changing characteristics of tested populations have implications for understanding post-pandemic infection trends and healthcare resource allocation.